PMA-qPCR method for the selective quantitation of viable lactic acid bacteria in fermented milk - Shi, Zihang; Li, Xiefei; Fan, Xiankang; Xu, Jue; Liu, Qing; Wu, Zhen; Pan, Daodong (Frontiers in Microbiology, 2022)
The number of viable lactic acid bacteria (LAB) is a key indicator of the quality of fermented milk. Currently, techniques, combining those of propidium monoazide (PMA) and qPCR have been applied to the quantification of viable bacteria in various matrices. In this research, the PMA-qPCR method was used to detect the number of viable bacteria of each LAB species in fermented milk. By analyzing pheS and 16S rRNA gene copy number and sequence similarities in five species of LAB, namely Lactobacillus delbrueckii subsp. bulgaricus, Lactiplantibacillus plantarum, Streptococcus thermophilus, Lactobacillus helveticus, and Lactococcus lactis subsp. lactis, the pheS gene resolved species identities better and was thus selected to design specific primers and probes. The pheS gene was cloned into the pUC19 vector and used to construct standard curve for absolute quantification. The standard curves for each LAB species were between 106 CFU/mL and 1011 CFU/mL, with an R2>0.99. The number of viable bacteria detected by PMA-qPCR was significantly lower than that of qPCR (P<0.05), which indicated that PMA inhibited the amplification of DNA from dead cells. This was corroborated by the results from bacterial staining and plate count experiments. Therefore, our PMA-qPCR method enabled rapid qualitative and quantitative determination of the number of viable bacteria in fermented milk.